2021
DOI: 10.1007/s00406-021-01291-7
|View full text |Cite
|
Sign up to set email alerts
|

Differential psychological response to the COVID-19 pandemic in psychiatric inpatients compared to a non-clinical population from Germany

Abstract: The COVID-19 pandemic is an inherently stressful situation, which may lead to adverse psychosocial outcomes in various populations. Yet, individuals may not be affected equally by stressors posed by the pandemic and those with pre-existing mental disorders could be particularly vulnerable. To test this hypothesis, we assessed the psychological response to the pandemic in a case–control design. We used an age-, sex- and employment status-matched case–control sample (n = 216) of psychiatric inpatients, recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 63 publications
(73 reference statements)
1
10
0
Order By: Relevance
“…International research has shown that these stressors might lead to reduced levels of well‐being within the population (e.g., South Korea: Kim et al., 2021 ; New Zealand: Sibley et al., 2020 ). German studies (Jung et al., 2020 ; Rek et al., 2021 ) found an average of 20% lower well‐being scores compared to a pre‐COVID‐19 norming sample (Brähler et al., 2007 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…International research has shown that these stressors might lead to reduced levels of well‐being within the population (e.g., South Korea: Kim et al., 2021 ; New Zealand: Sibley et al., 2020 ). German studies (Jung et al., 2020 ; Rek et al., 2021 ) found an average of 20% lower well‐being scores compared to a pre‐COVID‐19 norming sample (Brähler et al., 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the multiple stressors during the current pandemic and first evidence indicating a general reduction of well‐being (Jung et al., 2020 ; Rek et al., 2021 ), the present study aimed to (1) identify latent coping profiles in the German general population during the first year of the COVID‐19 pandemic and to (2) investigate differences between these profiles in well‐being.…”
Section: Introductionmentioning
confidence: 99%
“…During this COVID-19 pandemic, research demonstrated an increased level of mental health problems, e.g., anxiety, depression and somatization of people across population subgroups, especially in nonclinical population ( Dragioti et al., 2021 ; Hu et al., 2022 ; Zhang et al., 2022 ). The level of some symptoms, depression and loneliness due to COVID, were raised in nonclinical populations to the extent that nondifferences between clinical and nonclinical subjects were observed ( Rek et al., 2022 ). The role of self-report questionnaires, including OI-21, should be suitable for identifying and monitoring such mental health problems.…”
Section: Discussionmentioning
confidence: 99%
“…This culture-reactive hypothesis is aligned with the diathesis-stress model of psychopathology, which asserts that a person’s genetic or biological predisposition influences the probability of developing distress when a particular stressor is present [ 21 ]. The diathesis-stress model also appears to be supported by the recent tribulations of the SARS-COV-2 pandemic [ 22 ]. With the emergence of the pandemic, when lockdowns and social isolation were promoted to curb infection spread, there has been heightened reporting of the proliferation of loneliness and the development of something akin to HLID [ 23 25 ].…”
Section: Introductionmentioning
confidence: 94%